Quantifying and addressing the prevalence and bias of study designs in the environmental and social sciences - Alec P. Christie (Nature Portfolio, 2020)
Randomised controlled experiments are the gold standard for scientific inference, but environmental and social scientists often rely on different study designs. Here the authors analyse the use of six common study designs in the fields of biodiversity conservation and social intervention, and quantify the biases in their estimates.